2017
DOI: 10.1038/ni.3809
|View full text |Cite
|
Sign up to set email alerts
|

SMAD4 impedes the conversion of NK cells into ILC1-like cells by curtailing non-canonical TGF-β signaling

Abstract: Among the features that distinguish type 1 innate lymphoid cells (ILC1s) from natural killer (NK) cells is a gene signature indicative of ‘imprinting’ by cytokines of the TGF-β family. We examined mice in which ILC1s and NK cells lacked SMAD4, a signal transducer that facilitates the canonical signaling pathway common to all cytokines of the TGF-β family. While SMAD4 deficiency did not affect ILC1 differentiation, NK cells unexpectedly acquired an ILC1-like gene signature and were unable to control tumor metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
288
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(298 citation statements)
references
References 44 publications
(56 reference statements)
8
288
2
Order By: Relevance
“…MCMV infection also induces significant body weight loss. The magnitude of body weight loss is correlated with severity of viral infection . We next determined how alcohol consumption affects body weight change during the acute phase of MCMV infection.…”
Section: Resultsmentioning
confidence: 99%
“…MCMV infection also induces significant body weight loss. The magnitude of body weight loss is correlated with severity of viral infection . We next determined how alcohol consumption affects body weight change during the acute phase of MCMV infection.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Despite the effector potential of NK cells, they are usually dysfunctional in the tumour microenvironment. 16,17 Studies have proven the concept of, and have shown the potentials of, targeting some pathways for the reinvigoration of NK cell anti-tumour immunity. 16,17 Studies have proven the concept of, and have shown the potentials of, targeting some pathways for the reinvigoration of NK cell anti-tumour immunity.…”
Section: Nk Cells Are Anti-tumour Effector Cells Usually Dysfunctionamentioning
confidence: 99%
“…The presence of TGF‐β in the tumor microenvironment has been shown to decrease the responsiveness of NK cells, and it is also required for CD103 + tissue‐resident ILCs correct differentiation in many other tissues . A TGFβ‐dependent tumor immunoescape mechanism has been suggested as a NK cell transdifferentiation into non‐cytotoxic ILC1s consequences . Also in the PyMT‐driven tumors, both NK cells expressing Eomes and CD49a + and non‐NK ILC1‐like cells can be suppressed via TGFβ signals .…”
Section: Double‐edged Role Of Ilcs In Cancermentioning
confidence: 99%